Behavioral medicine: what it is and what it does - Touch Mercer, Gina (Henry Stewart Talks, 2022)
Definition of behavioral medicine, Components of behavioral medicine, Biopsychosocial Model, KSABs: Knowledge, Skills, Attitudes, and Behaviors associated with behavioral medicine, Behavioral medicine providers and settings, Outcomes of behavioral medicine, Institutional racism